Pengaruh Pembelajaran Berdiferensiasi Berbantuan Media Cartoon Story Maker Terhadap Kemampuan Menulis Teks Negosiasi Kelas X Di SMA Perguruan Teladan Medan - Samosir, Sarah Evelyn; Sitorus, Pontas Jamaluddin; Saragih, Elza L.L (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
This research aims to determine the effect of differentiated learning assisted by Cartoon Story Maker media on the ability to write negotiation texts for class X at Teladan Medan High School. This research is quantitative research that uses experimental methods with a two group posttest research design. The population studied was all class X students totaling 75 people and the samples in the research were class X1 with a total of 25 people and The data analysis techniques used include normality testing with the F test, homogeneity testing, and hypothesis testing. After carrying out the research, namely the posttest using Differentiated Learning assisted by the Cartoon Story Maker Application, the average score for the control class posttest was 54.6 and the experimental class posttest was 76. The results of hypothesis testing in this study obtained tcount>ttable (7.40 > 1, 98) thus, Ho is rejected and Ha is accepted and the test results of the posttest requirements are normally distributed and homogeneous. So it can be concluded that the Influence of Differentiated Learning Assisted by Cartoon Story Maker Media on the Ability to Write Negotiation Texts for Class X SMA Teladan Medan.